Multilingualism and Emotional Competence: Exploring Linguistic and Cognitive Dimensions - Kafia, A.A.; Rahman, A. (University of Jaffna, 2025)
Cognitive science has consistently demonstrated that multilingual individuals possess a cognitive advantage over monolingual. Similarly, linguistic research provides evidence that multilinguals can effectively separate their lexicons and grammatical structures traversing complex multilingual environments. However, how multilingualism impacts emotional competence (EC) remains under investigation. Prior studies have largely overlooked the role of cognitive flexibility in emotional regulation, leaving a gap in understanding how multilingual experiences shape emotional intelligence. This influence is mediated by linguistic and cognitive factors. Divergent thinking (DT) fosters creative problem-solving, allowing multilingual individuals to respond emotional situations with greater flexibility. Executive functions (EF) regulate cognitive control and decision-making, but excessive cognitive demands may interfere with emotional processing (Miyake & Friedman, 2012). Language switching (LS) enables smooth transitions between linguistic systems but may introduce cognitive challenges in emotional expression and increase mental fatigue. Similarly, cultural frame switching (CFS) allows individuals to adjust their communication styles based on cultural contexts, shaping emotional responses. This study explores two aspects of multilingualism and EC; i) investigating whether LS and CFS contribute to EC development, and ii) examining how DT and EF influence EC. The study was conducted among 42 non-Bangla speaking tribal EFL learners from various academic disciplines at a public university in Bangladesh. Participants enrolled in a one-semester English course (100 marks) covering Listening, Speaking, Reading, and Writing (L, S, R, W). Data collection involved; i) a socio biographical and linguistic background questionnaire, ii) a Language and Social Background Questionnaire (LSBQ) to assess multilingual experiences, iii) a Profile of Emotional Competence (PEC) to measure emotional awareness and regulation, and iv) pre-test and post-test assessments before and after the semester to evaluate changes in EC and cognitive abilities. A mixed-method research paradigm was employed to ensure a comprehensive analysis for a more nuanced understanding of multilingualism’s impact on EC. Findings revealed a significant relationship between multilingualism and EC. DT and CFS positively mediated this relationship, suggesting that cultural adaptability (CFS) and creative problem-solving (DT) enhance emotional 9 Department of ELT, UoJ - Aug. 11–13, 2025 intelligence. However, EF and LS negatively impacted EC, indicating that frequent LS may create cognitive overload, reducing the ability to regulate emotions effectively. Additionally, the cognitive demands of executive control (EF) may divert mental resources away from emotional awareness, impairing spontaneous emotional processing. These results emphasize the need to consider CFS and DT in understanding the intricate relationship between multilingualism and EC. Educators and researchers should integrate cultural adaptability and creative problem-solving strategies into language learning to enhance emotional resilience in multilingual learners. Addressing these dynamics can optimize cognitive flexibility and emotional intelligence. This study extends prior research by providing empirical evidence on how linguistic (LS, CFS) and cognitive (DT, EF) factors jointly shape emotional intelligence. Unlike earlier studies, it examines the negative impact of EF and LS on EC, challenging conventional assumptions and offering new insights into the complex interplay between multilingual cognition and emotional regulation.
Keywords: Multilingualism; Emotional competence; Cognitive dimensions; Divergent thinking; Executive functions; Language switching; Cultural frame switching